Type 2 Diabetes Mellitus And Hemoptisis Risk Factor In Lung Tuberculosis : A Case Control Study - Widhy Yudistira Nalapraya; Jaka Pradipta; Muhammad Ikhsan Mokoagow; Erlina Burhan (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Background: Diabetes mellitus (DM) is a risk factor for tuberculosis (TB) morbidity and mortality. Increasing cases of type 2 DM in the world increases the risk of developing TB. The frequency of DM in TB patients was reported to be around 10-15% and the prevalence of this infectious disease was 2-5 times higher in diabetic patients compared to non-diabetics. Hemoptysis is a respiratory symptom which can be life threatening. Tuberculosis and bronchiectasis are the two most common ethology of hemoptysis, while TB with DM are the cause of recurrent hemoptysis. Methods: This was case control study which used the medical records data of diabetic patients infected with TB who experienced hemoptysis and no hemoptysis, treated at Fatmawati General Hospital during 2017. Sampling method was total sampling. Results: There were 12 hemoptysis patients with DM comorbidity and 31 patients without DM comorbidity. As many as 58% of patients with DM had new cases of pulmonary TB and 42% had history of treatment completion. The correlation between hemoptysis of TB patients with DM compared to without DM obtained a relative risk of 1.535 (95% CI=0.677-2.618) Conclusion: The proportion of hemoptysis in TB patients with DM comorbidity was 10.3%. Diabetes Mellitus was a risk factor for hemoptysis 1.535 times higher compared to TB patients without DM but statistically not significant. (J Respir Indo. 2020; 40(3): 144-9)